Do Black and White Americans Hold Different Views on Marijuana Legalization? Analyzing the Impact of “The War on Drugs” on Racialized Perceptions of Legalizing Marijuana. - Kaminoff, Benjamin S. (Tufts University. Tisch Library., 2018)
This study examines whether Black and White Americans develop their views regarding the legalization of marijuana based on different life experiences and, specifically, their involvement with the criminal justice system and drug laws. It aims to investigate if Black Americans generate their views regarding marijuana legalization differently than Whites based on concerns about Blacks as a group and the experiences of Black communities with the criminal justice system. It relies on qualitative interviews of White and Black Americans (n = 7) over the age of 35. The results preliminarily show that while White Americans develop views on legalizing marijuana based on traditional notions of personal freedom and drug abuse, Black Americans generate their views based on “linked fate” conceptions of group interests related to the history of drug laws and the experiences of Blacks in the criminal justice system. The implications of these findings are discussed.